Interleukin-6 and Interleukin-10 Gene Polymorphisms in Patients with Chronic Periodontitis and Response to Treatment after 3 Years - Georgios S. Chatzopoulos; Aikaterini-Elisavet Doufexi; Sofia Zarenti; Menelaos Anastasopoulos; Anastasia Kouvatsi (University of Zagreb. School of Dental Medicine, 2020)
Objective: The aim of this study was to investigate whether genetic susceptibility to chronic peri-odontitis, conferred by the presence of the IL-6 -572GG genotype or the IL-10 -592A allele, influences the outcomes following a non-surgical periodontal therapy (NSPT)over a long period of time. Material and methods: Thirty-seven chronic periodontitis patients were divided into two groups according to genotype as susceptible (SCP) and non-susceptible (NSCP). All subjects were clinically evaluated at baseline and 3 years following NSPT. Blood samples were collected at baseline from the individuals who fulfilled the inclusion criteria. All participants received NSPT from a single periodontist who was blind to the genotype status of each patient. A statistical analysis was performed by comparing the variables between groups using the Mann-Whitney U test and between baseline and 3 years for each group using the Wilcoxon test. Results: The mean age of the population was estimated to be 47.68±8.64 years and it included 51.4% females, 48.6% smokers, and 45.9% alcohol consumers. Following a genetic analysis, 70.3% of patients were homozygous carriers of the IL-6 -572G (IL-6 SCP), and 46.0% of them were carriers, bleeding on probing, percentage of sites with 4-6mm and ≥7mm pocket depth and attachment loss) to all participants, but the treatment outcome NSCP individuals showed similar clinical parameters at baseline and at 3 years. Conclusions: Within the limitations of this 3-year prospective cohort study in Caucasians diagnosed with chronic periodontitis, individuals susceptible to periodontal disease as determined by the presence of the IL-6 -572GG genotype or the IL-10 -592A allele showed similar treatment outcome following NSPT.